2006
DOI: 10.1080/13651500500410216
|View full text |Cite
|
Sign up to set email alerts
|

A review on hyponatremia associated with SSRIs, reboxetine and venlafaxine

Abstract: Hyponatremia, defined as serum sodium below 135 mmol/l, is a potentially life-threatening condition and was shown to be more frequent in elderly and psychiatric patients. In the last years numerous case reports on SSRI- and venlafaxine-induced hyponatremia were published indicating a higher incidence than previously thought. Only few studies have been performed and the incidence reported varies widely from 4.6/1000 people to 25%. It is still unclear if any single SSRI shows a higher incidence of hyponatremia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 85 publications
(89 reference statements)
0
9
0
1
Order By: Relevance
“…Among internistic drugs, especially thiazide diuretics are reported to enhance the risk of HN. Taking into account the high co-morbidity of depression and arterial hypertension in the elderly and the higher prescribing rates of SSRIs in this group of patients, it seems obvious that these patients have a higher risk of developing HN (Egger et al 2006 ;Liu et al 1996 ;Smith, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Among internistic drugs, especially thiazide diuretics are reported to enhance the risk of HN. Taking into account the high co-morbidity of depression and arterial hypertension in the elderly and the higher prescribing rates of SSRIs in this group of patients, it seems obvious that these patients have a higher risk of developing HN (Egger et al 2006 ;Liu et al 1996 ;Smith, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Istnieje wiele danych na temat występowania hiponatremii po zastosowaniu selektywnych inhibitorów wychwytu zwrotnego serotoniny (SSRI) [27]. Wiele badań iż zarówno neuroleptyki klasyczne, jak i atypowe mogą wiązać się z pojawieniem polekowej hiponatremii [52].…”
Section: Leczenie Siadhunclassified
“…There are many reports on the occurrence of hyponatremia following the use of selective serotonin reuptake inhibitors (SSRIs) [27]. Many studies confirm that SSRIs are the most common iatrogenic cause of hyponatremia [28], and that one in every 200 SSRI patients develops hyponatremia [29].…”
Section: Siadh and Antidepressantsmentioning
confidence: 99%
“…It has therefore been suggested that serum sodium concentrations be corrected no faster than 0.5 mEq/L/h and 8-12 mEq/L in the first 24 hours, with complete correction over 48-96 hours. 2,26 Upon discontinuation of the SSRI, the time course of return to normal sodium concentrations has ranged from 48 hours to 6 weeks, with most cases resolving within 2 weeks. 2 There is a paucity of published data on rechallenge with the same drug.…”
Section: Treatment and Time Coursementioning
confidence: 99%
“…1 If untreated, hyponatremia can lead to seizure, coma, and respiratory arrest when serum sodium levels fall below 120 mmol/l. 2 Worldwide, the population is aging, with more prominent demographic shifts occurring in developed nations with the best access to health care. Aged persons are susceptible to depression at a rate that exceeds that of their younger peers.…”
Section: Introductionmentioning
confidence: 99%